Moral Values in the Novel “Pasta Kacang Merah” By Durian Sukegawa: A Literary Sociology Approach - Pinta Ria Saragih; Ikhwanuddin Nasution; Nurhayati Harahap (Peneliti.net, 2026)
This study aims to describe the moral values ​​contained in the novel